CHROMIC ACID ANODIZING PROCESS OF ALUMINUM ALLOY 2024 T3 AND THE INFLUENCE OF CONCENTRATION OF DISSOLVED Al2O3 ON THE CHARACTERISTIC AND THE CORROSION RESISTANCE OF THE ANODIZE LAYER - LAKSANA ACHMAD (NIM : 22109012), TRIA
Al 2024 is the aluminum alloy with copper as the principal alloying element. This alloy is used for the fuselage. However, this alloy is more susceptible to localized corrosion. In order to increase the corrosion resistance of the alloy,then it is anodized in chromic acid solution. Chromic acid solution for the specifications of CASA, Boeing, Bombardier and Eurocopter shall havethe concentrations of dissolved Al2O3does not exceed 10 gpl. A restriction on the concentrations of dissolved Al2O3in chromic acid solution is one of the current issues in PT Dirgantara Indonesia (PT DI) due to the usage limit of the solution. A series of anodizing experiments in chromic acid solution has been conducted to study the influence of concentrations of dissolved Al2O3and its interactions with temperature, cell voltage andanodizing time on the weight and thicknessof anodize layer produced on Al 2024 T3as well as on itscorrosion resistance. Materialwhich is used in these experiments is aluminum alloy Al 2024 T3 bare with the dimension of110 x 30 x 1 mm3. Anodizing experimentsare preceded by smoothing the surface of the sample with abrasive paper then washed with alcohol in an ultrasonic cleaner for 2 minutes, alkaline cleaning with Turco 4215 S for 2 minutes and pickling with Turco smut for 1 minute. Chromic acid solutionswhich areused contain 40 gpl free CrO3 and 0, 13 and 25 gplAl2O3 dissolved. The anodizing processwas carried out by adjusting the cell voltage at 20 and 40 V with a rectifier. The initial potential is increasedstage by stage (4 V per minute) until it reaches a design constant voltage (20 and 40 V). At each voltage, the anodizing is conducted for 40 and 60 minutes and at a temperature of 25 and 35 0C. Porous anodized layer are formed after anodizing in chromic acid solution and it shall be sealed to increase the corrosion resistance. Sealing was carried out by immersing the sample into dilute chromate solution at a temperature of 930C for 28 minutes. Each experimenthas been performed twice. Salt spray test has been done according to ASTM B117 standard. The sample is hold with a slope of 150from the vertical axis on a salt spray chamber. Salt spray test has been done using 5% NaCl solution at a temperature of 35 0C for 336 hours. According to the four-factors analysis of variance (ANOVA), the sequence of the factors that most influencinganodize layer weight prior to sealing and anodize layer thickness after sealing in general is the temperature, concentrations of dissolved Al2O3, anodizing time and cell voltage. Al2O3which is dissolved in chromic acid solution decreased the weight and thickness of anodized layer,resulted from the reduction in the average of current density generated. According to the least significance difference(LSD) test,there is no significant decreased of the weight and thickness of anodized layer in a solution which containsdissolved Al2O3of 0 to 13 gpl. The decreased of the weight and thickness of anodized layer became significant and inferior after the Al2O3dissolved concentrations exceeds 13 gpl.The influence of interactions between anodizing process variables is controlled by the concentrations of dissolved Al2O3.Increasing temperature (from 25 up to 35 0C), anodizing time (from 40 up to 60 minutes) and cell voltage (from 20 up to 40 V) in anodize solution containing 25 gpl of dissolved Al2O3 does not significantly increased the weight and thickness of anodized layer produced. Corrosion resistance of anodize layeris proportional to the thickness of anodized layer produced. The maximum corrosion resistance occurs when the thickness of anodized layer producedis above 4 μm. According to the response surface and contour plot of the most influential factors, the recommended temperature of the anodizing process in chromic acid solution is above 33 0C to 35 0C and the maximum concentrations of dissolved Al2O3 in the bath is 15 gpl.